On Some Fixed Point Results in E−Fuzzy Metric Spaces. (20th September 2021) - Mecheraoui, Rachid; Mitrović, Zoran D.; Parvaneh, Vahid; Aydi, Hassen; Saleem, Naeem
Abstract : In the existing literature, Banach contraction theorem as well as Meir-Keeler fixed point theorem were extended to fuzzy metric spaces. However, the existing extensions require strong additional assumptions. The purpose of this paper is to determine a class of fuzzy metric spaces in which both theorems remain true without the need of any additional condition. We demonstrate the wide validity of the new class.